Pengaruh Employability Skills Terhadap Kinerja Taruna Praktik Kerja Lapangan Sekolah Tinggi Teknologi Kedirgantaraan - Putri Sugi Fitriasih; Anita Nur Masyi’ah (Ebisnis Manajemen, 2025)
The increasingly rapid aviation industry demands the world of work to have quality human resources, the demand for higher performance requires a workforce with academic qualifications and employability to be said to be feasible. The College of Aerospace Technology provides a field work practice program where cadets will face challenges and various obstacles in the new work environment, therefore employability skills are needed that can affect the performance given during the field work practice period. This study aims to analyze the influence of employability skills on the performance of cadets in field work practice, as well as to identify how much influence employability skills have on the performance of cadets in field work practices. This study uses a quantitative method, the research was conducted at Sekolah Tinggi Teknologi Kedirgantaraan as the location for sampling students os the D4 Air Transport Management study program, and the research was carried out from September to May 2025 with the number of cadets of the D4 Air Transportation Management of the College of Aerospace Technology as many as 188 cadets. The data collection technique in this study used questionnaires, interviews and documentation. The data analysis technique used normality tests, simple linear regression tests, T tests and determination efficiency tests. The results of the study showed that there was a significant influence of employability skills on the performance of cadets practicing field work, with a score of Thitung > Ttabel (18,671 > 1,973) and an Rsquare value of 65.2% so that it can be said that Ha was accepted. Suggestions for future researchers are expected to develop this study by adding other variables related to cadets' performance during fieldwork practices by expanding the population coverage.